Late Pleistocene-Holocene earthquake-induced slumps and soft-sediment deformation structures in the Acequion River valley, Central Precordillera, Argentina - Perucca, Laura P.; Godoy, Enrique; Pantano, Ana (Bogucki Wydawnictwo Naukowe, 2014)
Evidence of earthquake-induced liquefaction features in the Acequión river valley, central western Argentina, is ana -lysed. Well-preserved soft-sediment deformation structures are present in Late Pleistocene deposits; they include two large slumps and several sand dikes, convolutions, pseudonodules, faults, dish structures and diapirs in the basal part of a shallow-lacustrine succession in the El Acequión River area. The water-saturated state of these sediments favoured deformation. All structures were studied in a natural trench created as a result of erosion by a tributary of the Acequión River, called El Mono Creek. They form part of a large-scale slump system. Two slumps occur in the western portion of the trench and must have moved towards the ENE (70°), where the depocentre of the Boca del Acequión area is situated. Consid -ering the spatial relationship with Quaternary faults, the slumps are interpreted as being due to a seismic event. The thickest dikes in the El Mono Creek trench occur in the eastern portion of the trench, indicating that the responsible earthquake was located to the east of the study area, probably at the Cerro Salinas fault system zone. The slumps, sand dikes and other soft-sediment deformation features are interpreted as having been triggered by earth -quakes, thus providing a preliminary palaeoseismic record of the Cerro Salinas fault system and extending the record of moderate- to high-magnitude earthquakes in central western Argentina to the Late Pleistocene.
Keywords: Lacustrine sedimentation; Liquefaction; Seismites; Slumps; Soft-sediment deformation structures; Palaeo-earthquakes